2013
DOI: 10.1007/s00284-013-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of HpmA and HlyA Hemolysin of Uropathogenic Proteus mirabilis

Abstract: Urinary tract infection (UTI) is one of the bacterial infections frequently documented in humans. Proteus mirabilis is associated with UTI mainly in individuals with urinary tract abnormality or related with vesicular catheterism and it can be difficult to treat because of the formation of stones in the bladder and kidneys. These stones are formed due to the presence of urease synthesized by the bacteria. Another important factor is that P. mirabilis produces hemolysin HpmA, used by the bacteria to damage the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
6
28
1
Order By: Relevance
“…P. mirabilis produce two toxins, haemolysin (HpmA) and Proteus toxic agglutinin (Pta), which are implicated in tissue damage and dissemination to the kidneys, initiating acute pyelonephritis 16,72 . HpmA is a Ca + -dependent pore-forming cytolysin that destabilizes the host cell by inserting itself into the cell membrane and causing a Na + efflux 16 (FIG.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…P. mirabilis produce two toxins, haemolysin (HpmA) and Proteus toxic agglutinin (Pta), which are implicated in tissue damage and dissemination to the kidneys, initiating acute pyelonephritis 16,72 . HpmA is a Ca + -dependent pore-forming cytolysin that destabilizes the host cell by inserting itself into the cell membrane and causing a Na + efflux 16 (FIG.…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…For example, hpmA was found by Southern blot in 63/63 isolates tested, and correlated with hemolytic activity (102); likewise, a survey of 211 isolates using a combination of PCR and dot blot found that all encoded hpmA (103). Zap protease is also widespread, including all P. mirabilis tested from a diverse O-serogroup collection (104).…”
Section: Approaches To Studying Virulencementioning
confidence: 99%
“…The calcium-independent hemolysin is encoded by two genes comprising a two-partner secretion system: hpmA , which produces a 166 kDa secreted exoprotein, and hpmB , which produces a 63 kDa translocase protein that is required for both the activation and secretion of HpmA through cleavage of an N-terminal peptide (209). HpmA is the predominant hemolysin in Proteus species and appears to be the only hemolysin encoded by P. mirabilis , present in 268/274 (98%) of P. mirabilis clinical and fecal isolates from Brazil and the United States while none of these isolates encoded hlyA (102, 103). Similarly, hpmA is present in all 7 complete P. mirabilis genome sequences available through NCBI as of May 2017.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…The hemolysin is encoded by hpmA , while a second gene, hpmB , encodes a membrane transporter; both genes are highly conserved across P. mirabilis isolates (220). The levels of hemolysin in P. mirabilis correlate with its ability to invade cultured kidney cells, and an isogenic P. mirabilis Δ hpmA mutant is minimally invasive in cultured cells (136, 137).…”
Section: Trimeric Autotransportersmentioning
confidence: 99%